1984
DOI: 10.1002/macp.1984.021850606
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the valence state of titanium in MgCl2‐supported titanium catalysts on olefin polymerization

Abstract: The relationships between the valence state of titanium in MgCI,-supported titanium catalysts and polymerization performances for ethylene and propylene were studied. When the titanium species of the supported titanium catalyst 1 was preliminarily reduced by treating it with AlEt3, the resulting catalyst system 2 had lost the activity for propylene polymerization completely. The catalyst activity for ethylene polymerization was found to be reduced to 20% of that of the original catalyst 1. In the AlEt3-pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(90 citation statements)
references
References 8 publications
3
86
1
Order By: Relevance
“…The limiting factor appeared to be the transfer processes across the external film boundary layer, where again initial particle size was critical. For high-activity catalyst with a diameter of 30 pm and a particle moving at a speed of 20 cm -s-l a temperature difference across the layer was estimated at 10 K. A particle of 10 pm had a A T < 1 K. Floyd et al" investigated differing particle velocities and found that a greater velocity lowered AT. The particle velocity of this reactor system, if evaluated at the edge of the stir blades, is about 163 cm -s-', eight times the largest velocity considered by Floyd et al, so A T in this system should be further reduced ( < 1 K ) .…”
Section: Heat Transfermentioning
confidence: 99%
“…The limiting factor appeared to be the transfer processes across the external film boundary layer, where again initial particle size was critical. For high-activity catalyst with a diameter of 30 pm and a particle moving at a speed of 20 cm -s-l a temperature difference across the layer was estimated at 10 K. A particle of 10 pm had a A T < 1 K. Floyd et al" investigated differing particle velocities and found that a greater velocity lowered AT. The particle velocity of this reactor system, if evaluated at the edge of the stir blades, is about 163 cm -s-', eight times the largest velocity considered by Floyd et al, so A T in this system should be further reduced ( < 1 K ) .…”
Section: Heat Transfermentioning
confidence: 99%
“…We reported direct evidence of EB transforming the aspecific sites into highly stereospecific sites. 14 We invested enormous effort to reveal the roles and behavior of EB, [15][16][17][18] enabling us to discover more effective electron donors (as described subsequently). For example, Figure 5 demonstrates the relation of the amount of EB and the activities.…”
Section: 12mentioning
confidence: 99%
“…Industrial catalysts produce Ϸ100-500 g polypropylene per g catalyst per hr⅐atm and Ϸ2,000-10,000 g polyethylene per g catalyst per hr⅐atm (9). The fact that the model catalysts exhibit activities similar to the industrial catalysts suggests that the surface properties of the model catalysts prepared in UHV are relevant to those of industrial catalysts (25,26). Single-site propylene polymerization.…”
Section: Resultsmentioning
confidence: 99%